2018
DOI: 10.1177/1559325818789841
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Photothermal Therapy on Osteosarcoma With Polyacrylic Acid–Coated Gold Nanorods

Abstract: Background:Polyacrylic acid (PAA)–coated gold nanorods (GNRs) were prepared in this research, and then the structure, stability, temperature increment efficiency, and biocompatibility of GNRs@PAA were detected.Methods:It was demonstrated that GNRs@PAA coupled with an 808 nm laser had superior efficiency of hyperthermia therapy for MG63 human osteosarcoma cell.Results:The mechanism of photothermal therapy of GNRs@PAA was explored, and it was proved that damaged cell membrane and DNA integration caused cell apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Over the past few decades, many nanoparticles‐based delivery systems have been developed and employed in clinical diagnosis and therapy (Z. Chen et al, ; Z. Chen et al, ; Ma et al, ; Pan et al, ; Z. Yang et al, ; C. Zhou, Yang, & Teng, ). For cancer immunotherapy, nanoparticle‐based platforms can be divided into two types according to the substrate component: naturally derived nanoparticles and synthetic nanoparticles.…”
Section: Nanoparticle‐based Platforms For Cancer Immunotherapymentioning
confidence: 99%
“…Over the past few decades, many nanoparticles‐based delivery systems have been developed and employed in clinical diagnosis and therapy (Z. Chen et al, ; Z. Chen et al, ; Ma et al, ; Pan et al, ; Z. Yang et al, ; C. Zhou, Yang, & Teng, ). For cancer immunotherapy, nanoparticle‐based platforms can be divided into two types according to the substrate component: naturally derived nanoparticles and synthetic nanoparticles.…”
Section: Nanoparticle‐based Platforms For Cancer Immunotherapymentioning
confidence: 99%
“… 6 - 8 In particular, it can reduce the side effects of chemotherapy on patients, reduce the adverse events caused by chemotherapy, improve the quality of life of patients, and prolong the survival time. 9 - 13 Several recent studies have shown that nanomaterials can penetrate biofilms and enter cells, tissues, and organs that larger size particles usually cannot penetrate, delivering drugs to locations that are difficult to reach with conventional chemotherapy drugs. 14 - 18 There are currently several formulations based on NPs delivery on the market, and others are at different stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…The samples are incubated for different periods (12 hours, 1 day, and 3 days) at 37 C under the humidified atmosphere (5% CO 2 ) and in dark. Established Cell Counting Kit 8 (CCK-8) assays, recognized as one typical method for measuring cell viability, 16 are performed to assess the metabolic activity of cells exposed to the SiNWs. With different incubation time, 10 mL of stock CCK-8 reagents are added to each well, and cells are then incubated for 4 hours at 37 C. Absorbance is measured at 450 nm using microplate reader (Bio-Rad 680; Bio-Rad, Hercules, CA).…”
Section: Cell Counting Kit 8 Assay and Cell Morphology Observationmentioning
confidence: 99%